(untitled) (Faridpur Medical College Journal, 2011)
Cardiovascular diseases are the commonest cause of death globally and are the major contributor to the burden of premature mortality and morbidity. This study analyses various clinical presentations, conventional risk factors, pattern and severity of coronary heart disease on angiography among 637 patients with coronary heart disease and adult congenital heart disease who underwent cardiac evaluation at National Institute of Cardiovascular Disease (NICVD), Dhaka between January 2007 to December 2008. Among them 547 (85.9%) were male and 90 (14.1%) were female. All of them were between 22 to 76 years of age with mean age 50.15±8.8. One hundred sixty nine (25.9%) patients had chronic stable angina & 398 (62.48%) patients subjected for coronary angiography for acute coronary syndrome and or old myocardial infarction and 74 (11.62%) patients with vascular and adult congenital heart disease prior to surgical treatment. Most prevalent risk factors were smoking (60%) and dyslipidaemia (60%). Thirty five percent patients were hypertensive and 10% patient had diabetes. Normal epicardial coronaries were documented in 25.59% patients which includes the patients who underwent coronary angiography prior to surgical treatment. Ninety three (14.6%) had single vessel disease, 119 (18.68%) had double vessel disease, 259 (40.66%) had triple vessel disease and 3 (0.47%) had isolated left main disease. Key words: Coronary angiogram; Coronary artery disease. DOI: http://dx.doi.org/10.3329/fmcj.v6i2.9206 FMCJ 2011; 6(2): 82-85